Impact of Multinational Corporations in the Practice of Nigerian Diplomacy - Paul , Nwala; Amugo, Frank O. (Kashere Journal of Politics and International Relations, 2024)
Multinational corporations most times influence the diplomatic practice of their host countries by shaping their economic and political dynamics through their socioeconomic operations and representations of their home country's interests. This is because the significant investments of these multinational corporations facilitate increased diplomatic engagements to ensure favourable conditions for business. Furthermore, the presence of multinational corporations has increasingly become a determining factor in the conception and implementation of foreign policy by states. Thus, this paper explores the multifaceted issues and prospects emanating from the advent of multinational corporations on Nigeria’s diplomacy, examining the interplay between economic interests and diplomatic ties. It delves into how multinational corporations have influenced Nigeria’s foreign policy making and Diplomatic practices. A historical method through mostly secondary sources of data is employed to highlight instances where the investments of multinational corporations and their activities thereof had formed the basis for diplomatic decisions and how it has informed Nigeria’s stance on global issues. The reciprocal nature of the nexus between foreign policy making and multinational corporations is examined, capitalizing on the evolving dynamics between multinationals and Nigerian diplomacy, thereby contributing to a nuanced understanding of the complex interaction between economic forces and diplomatic activities in general.